Analysis of factors influencing financial inclusion of coffee farmers in the littoral region of Cameroon - Bate, N. G. S. (Strathmore University, 2024)
The study delves into the determinants of financial inclusion among coffee farmers in the Littoral region of Cameroon, aiming to uncover factors influencing their engagement with the financial system. By analyzing individual farmer characteristics, farm farm business characteristics, and Microfinance Institutions (MFIs), the research seeks to elucidate their roles in fostering financial inclusion, including aspects like savings accounts and loan accessibility. Data collected from 300 respondents across rural areas will address knowledge gaps and provide insights into the relationship between financial inclusion and coffee farming. Utilizing Principal Component Analysis (PCA), an FI Index will be constructed to measure financial inclusion comprehensively. Correlation results reveal a significant and negative correlation between MFIs and Farm business characteristics (-0.391, p < 0.01), and no significant correlation between MFIs and Farmer Characteristics (0.083, p = 0.493), while Farm business characteristics demonstrate a moderate and significant positive correlation with Farmer Characteristics (0.319, p < 0.01). The findings suggest that Farm business characteristics and Farmer Characteristics positively influence financial inclusion, emphasizing the importance of fostering entrepreneurial skills among coffee farmers. The study proposes recommendations for policy and practice, including strengthening financial literacy programs, supporting entrepreneurship, improving access to financial services, enhancing collaboration, promoting policy reforms, and monitoring interventions. Further research avenues include longitudinal studies, comparative analyses, qualitative research, impact evaluations, policy analysis, and advocacy to deepen understanding and address limitations, ultimately contributing to inclusive development in the region.
Full - text thesis